The Dynamics of Waqf in Islamic Civilisation: From the Prophet's Time to the Modern Era - Sa'adillah, Rangga; Roesli, Mohammad; Robbani, Shofa; Imroatul Azizah; Muhammad Irfanudin Kurniawan (VRISPRAAK : International Journal of Law, 2023)
Waqf is a concept in Islam that refers to the gift of property that is eternally useful for benevolent purposes. The history of waqf dates back to the time of Prophet Muhammad SAW, where he and his companions practised waqf as a means to fulfil the social and religious needs of the community. Initially, waqf was used to build mosques, madrasas, and provide public facilities such as wells and roads. The development of waqf continued during the Islamic Caliphate, with the establishment of various waqf institutions that supported education, health, and public infrastructure. In the modern era, the concept of waqf underwent a transformation with applications in broader economic and social fields, including the professional management of waqf assets to ensure the sustainability of its benefits. The history of waqf demonstrates its important role in the development of Islamic civilisation and its contribution to the welfare of society as a whole.